Vibration characteristics investigation of sandwich composite materials of uni-directional and twill carbon fibers. (December 2021) - Ula, Nur Mufidatul; Wijaya, Yusuf Giri; Muksin,; Mikhael Gilang, P.P.P.; Muzayadah, Nurul Lailatul; Ramadhan, Redha Akbar
Abstract: Vibration testing has carried out on the sandwich material composite specimen. This study aimed to determine the vibration characteristics of carbon-based sandwich composites. Sandwich composites were made by using the Vacuum assisted resin infusion method with two types of fiber directions, unidirectional and twill. The resin used for the sandwich composite was Vinyl Ester with Divinycell foam as the core. Each fiber direction was varied with 3 layers configurations, namely 2C2, 3C3 and 4C2. From the research results, it was found that the natural frequency in the twill fiber was smaller than the natural frequency in the unidirectional direction. The damping properties of both also indicate that the pattern of loss factor values in the UD fiber direction was more stable than the composite with the twill fiber direction. Research with the variations of fibers, resins, cores, and other components are needed to obtain a more complete dynamic characteristic database.